ChemInform Abstract: Diethylzinc‐Mediated Addition of 2, 2‐Dibromo‐2‐fluoroacetamides to Carbonyl Compounds: Synthesis of α‐Bromo‐α‐fluoro‐β‐hydroxy Amides and/or (Z)‐Fluorovinyl Amides. Issue 45 (14th October 2013) - Lemonnier, Gerald; Poisson, Thomas; Couve‐Bonnaire, Samuel; Jubault, Philippe; Pannecoucke, Xavier
Abstract Depending on the nature of the amide, diethylzinc‐mediated additions of 2, 2‐dibromo‐2‐fluoroacetamides to aldehydes, ketones or imine afford selective access either to bromofluorohydrins or to (Z)‐α‐fluoroacrylamides.